Facile synthesis of novel carbon quantum dots from biomass waste for highly sensitive detection of iron ions. (April 2020) - Wang, Cunjin; Shi, Huanxian; Yang, Min; Yan, Yujia; Liu, Enzhou; Ji, Zhen; Fan, Jun
Graphical abstract: Highlights: Biomass waste was used to prepare high performance carbon quantum dots. The prepared biomass carbon quantum dots exhibit sensitivity to Fe 3+ ions and pH. The biomass CQDs realized the quantitative detection of Fe 3+ ions in pond water. Abstract: In this work, some common and inexpensive biomass waste were used as carbon sources including orange peel, ginkgo biloba leaves, paulownia leaves and magnolia flower to prepare biomass carbon quantum dots (CQDs) by using a facile hydrothermal process. These biomass CQDs exhibited the advantages of homogeneous particle size, superior water solubility and stability, similar optical properties and surface functional group. The fluorescence quenching effect was observed when Fe 3+ ions were added into CQDs solution. The experiment results showed that the as-prepared CQDs have a sensitive response to Fe 3+ ions in the concentration range of 0.2−100 μM, and the limit of detection (LOD) could as low as 0.073 μM. More importantly, practical applications for the detection Fe 3+ ions in pond water acquired satisfactory recoveries (94 %–108 %). Therefore, this work not only provided a new way for reusages of biomass waste, but also provided a novel alternative sensor for Fe 3+ ions detection in real-world.